Ultrasound-assisted Synthesis of Some New Curcumin Analogues and Their Corresponding Pyrazoline Derivatives - Hawaiz, Farouq E.; Shekh Omer, Dlzhen A. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2017)
In this work, a series of new curcumin mono-carbonyl analogs containing benzyloxy moieties and their pyrazoline derivatives were synthesized using a green method (ultrasound assisted technique) along with traditional method. The work also includes a comparison between the two methods together and with literature. Remarkable improvements were achieved by dropping down the reaction time from hours to minutes and obtaining higher yields of the products.